Design and Implementation of an Electronic Device for Water Level Monitoring and Automated Pump Control in Tanks - Bekkouche Younes; Hamidi Abdallah; Djedid Oussama (University of Shahid Hama Lakhdar - El Oued, 2025)
Water management is a critical challenge in modern infrastructure, especially in regions facing water scarcity and growing urban demands. Manual monitoring of water tank levels is inefficient, often leading to overflow, dry running, and energy waste. This thesis presents the design and implementation of a smart water level detection and notification system using an Arduino-based platform. The system employs an ultrasonic sensor for non-contact water level measurement, a relay module for automatic pump control, and a GSM module for real-time SMS alerts. The hardware setup includes the Arduino Uno (ATmega328P), HC-SR04 ultrasonic sensor, ACS712 current sensor, SIM800L GSM module, and supporting components like a breadboard and relay circuits. The software was developed using the Arduino IDE, integrating sensor data acquisition, threshold-based logic, and communication protocols. Performance analysis shows the system provides accurate level detection, reliable relay switching, and stable remote notifications. The project demonstrates a low-cost, scalable, and energy-efficient solution suitable for domestic and industrial water management. Future work includes mobile app integration, solar-powered deployment, and multi-tank monitoring. تُعد إدارة المياه من التحديات الحيوية في البنية التحتية الحديثة، لا سيما في المناطق التي تعاني من ندرة المياه وزيادة الطلب الحضري. إن المراقبة اليدوية لمستويات خزانات المياه غير فعّالة، وغالبًا ما تؤدي إلى فيضانات، أو تشغيل المضخات في حالة الجفاف، مما يُسبب هدراً في الطاقة والمياه. يهدف هذا البحث إلى تصميم وتنفيذ نظام ذكي لرصد مستوى المياه وإرسال الإشعارات باستخدام منصة أردوينو. يعتمد النظام على مستشعر ألتراسونك لقياس مستوى المياه بدون تلامس، بالإضافة إلى وحدة ريليه للتحكم التلقائي في تشغيل المضخة، ووحدة GSM لإرسال تنبيهات عبر الرسائل النصية في الوقت الحقيقي. يتكوّن النظام من لوحة Arduino Uno (ATmega328P) ، مستشعر HC-SR04 ، مستشعر التيار ACS712 ، وحدة SIM800L ، ولوحة تجريبية (breadboard) مع الدوائر المساعدة. تم تطوير البرنامج باستخدام بيئة Arduino IDE ، حيث تم دمج برمجيات لقراءة المستشعرات، وتنفيذ منطق التحكم وفقًا لحدود محددة، وإرسال التنبيهات. أظهرت نتائج التقييم أن النظام يتميز بدقة عالية في قياس المستوى، واستقرار في تشغيل وإيقاف المضخة، وموثوقية في التنبيهات البعيدة. يُعد المشروع حلاً منخفض التكلفة، قابلاً للتوسع، وفعالاً في استهلاك الطاقة، ومناسبًا لتطبيقات سكنية وصناعية. وتشمل التوسعات المستقبلية تطوير تطبيق جوال، واستخدام الطاقة الشمسية، ودعم أنظمة متعددة الخزانا ت .
Master's thesis in electromechanics
Keywords: Arduino; water level detection; ultrasonic sensor; GSM module; automatic pump control; smart monitoring; embedded systems; أردوينو، مراقبة مستوى المياه، مستشعر ألتراسونك، وحدة GSM ، التحكم التلقائي بالمضخة، الأنظمة المدمجة، التنبيه الذكي